Implementation of the Apostille Service Policy in Indonesia - Sri Wahyuli Debora Sinaga; Achmad Lutfi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Legalization of Apostille, hereinafter referred to as Apostille, is the act of certifying the signature of an official, the ratification of a stamp, and/or the official seal in the requested document based on verification. Based on Presidential Regulation Number 2 of 2021 dated January 4, 2021, concerning the Ratification of the Convention Abolishing the Requirement of Legalisation for Foreign Public Documents, and the Regulation of the Minister of Law and Human Rights Number 6 of 2022 dated January 21, 2022, concerning Apostille Legalization Services in Public Documents, this regulation emphasizes changes in the legalization process. The convention simplifies the legalization procedure by certifying document signatures in member states through Apostille documents issued by the Competent Authority. In Indonesia, the Competent Authority appointed is the Ministry of Law and Human Rights of the Republic of Indonesia, specifically the Directorate General of General Legal Administration. The Apostille Convention was motivated by the previously multi-layered legalization process at various levels, which typically took more than 14 working days and involved additional costs at each stage. This study aims to determine the implementation of the Apostille service policy in Indonesia and the factors influencing its implementation. The research employs a qualitative descriptive method, collecting primary data through interviews and secondary data through literature studies and documentation. The findings conclude that the implementation of the Apostille service in Indonesia has been successfully carried out, as evidenced by a total of 154,891 applicants since the Apostille Service was officially launched on June 14, 2022. However, the Apostille service still faces several obstacles in practice. More intensive socialization efforts and stronger support from relevant stakeholders are needed to ensure the continued success of this Apostille service.